Genomic-based taxonomic classification of the family Erythrobacteraceae - Xu, Lin; Sun, Cong; Fang, Chen; Oren, Aharon; Xu, Xue-Wei (International journal of systematic and evolutionary microbiology, 2020)
The family Erythrobacteraceae , belonging to the order Sphingomonadales , class Alphaproteobacteria , is globally distributed in various environments. Currently, this family consist of seven genera: Altererythrobacter , Croceibacterium , Croceicoccus , Erythrobacter , Erythromicrobium , Porphyrobacter and Qipengyuania . As more species are identified, the taxonomic status of the family Erythrobacteraceae should be revised at the genomic level because of its polyphyletic nature evident from 16S rRNA gene sequence analysis. Phylogenomic reconstruction based on 288 single-copy orthologous clusters led to the identification of three separate clades. Pairwise comparisons of average nucleotide identity, average amino acid identity (AAI), percentage of conserved protein and evolutionary distance indicated that AAI and evolutionary distance had the highest correlation. Thresholds for genera boundaries were proposed as 70 % and 0.4 for AAI and evolutionary distance, respectively. Based on the phylo-genomic and genomic similarity analysis, the three clades were classified into 16 genera, including 11 novel ones, for which the names Alteraurantiacibacter , Altericroceibacterium , Alteriqipengyuania , Alteripontixanthobacter , Aurantiacibacter , Paraurantiacibacter , Parerythrobacter , Parapontixanthobacter , Pelagerythrobacter , Tsuneonella and Pontixanthobacter are proposed. We reclassified all species of Erythromicrobium and Porphyrobacter as species of Erythrobacter . This study is the first genomic-based study of the family Erythrobacteraceae , and will contribute to further insights into the evolution of this family.